The effect of giving lavender aromatherapy on anxiety level in final stage students of DIII midwifery at aisyah university of pringsewu - Septika Yani Veronica; Riza Dwiningrum (Universitas Aisyah Pringsewu, 2023)
Anxiety that arises when facing exams will affect student performance and test failure. Students who experience low anxiety can still give better performance than those who experience moderate and high anxiety. The purpose of this study was to determine the effect of giving Lavender Aromatherapy with Anxiety Levels in Final Year DIII Midwifery Students at Aisyah University of Pringsewu in 2021. This type of research is quantitative with a quasi-experimental research design and uses a research approach, namely one group pretest-posttest. The population in this study was the final year DIII Midwifery student at Aisyah University of Pringsewu. This sample research is the final year DIII Midwifery student at Aisyah University of Pringsewu who lived outside the dormitory as many as 18 female students. The sampling technique in this study used purposive sampling. The result of this research is the p-value is 0.000 or p-value less than 0.05, which means that there is an influence of the Effect of Lavender Aromatherapy on Anxiety Levels in Midwifery Final Year Students at Aisyah University of Pringsewu in 2021. That it can be used as a means to increase insight, experience, knowledge development and practice to overcome anxiety on DIII Midwifery students by always routinely using lavender aromatherapy and visiting health services. Abstrak: Kecemasan yang muncul saat menghadapi ujian akan mempengaruhi kinerja siswa dan kegagalan ujian. Siswa yang mengalami kecemasan rendah masih dapat memberikan kinerja yang lebih baik dibandingkan siswa yang mengalami kecemasan sedang dan tinggi. Tujuan penelitian ini adalah untuk mengetahui pengaruh pemberian Aromaterapi Lavender terhadap Tingkat Kecemasan pada Mahasiswa DIII Kebidanan Universitas Aisyah Pringsewu Tahun 2021. Jenis penelitian ini adalah kuantitatif dengan desain penelitian quasi eksperimen dan menggunakan pendekatan penelitian yaitu one group pretest-posttest. Populasi dalam penelitian ini adalah mahasiswa tingkat akhir DIII Kebidanan Universitas Aisyah Pringsewu. Sampel penelitian ini adalah mahasiswa tingkat akhir DIII Kebidanan Universitas Aisyah Pringsewu yang tinggal di luar asrama sebanyak 18 mahasiswi. Teknik pengambilan sampel dalam penelitian ini menggunakan purposive sampling. Hasil dari penelitian ini adalah p-value 0,000 atau p-value kurang dari 0,05 yang artinya ada pengaruh Pengaruh Aromaterapi Lavender Terhadap Tingkat Kecemasan Pada Mahasiswa Akhir Kebidanan Universitas Aisyah Pringsewu Tahun 2021. Sehingga dapat dapat digunakan sebagai sarana untuk menambah wawasan, pengalaman, pengembangan pengetahuan dan praktik untuk mengatasi kecemasan pada mahasiswa DIII Kebidanan dengan selalu rutin menggunakan aromaterapi lavender dan mengunjungi pelayanan kesehatan.